Penyelesaian Dugaan Pelanggaran Ham pada Kantor Wilayah Kementerian Hukum dan Ham Provinsi Bali - Ni Ketut Sinta Masdewi; Ida Ayu Putu Widiati; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2020)
The allegations of human rights violation in the Province of Bali whether done vertically by the government or horizontally by the fellow society, were noted through the high number of the people’s report, which were flowing to the team of the Public Communication Service in the Regional Office of The Legal and Human Rights Ministries of Bali. The issues to be elaborated in this research are as set forth how is the mechanism in resolving the allegations of Human Rights violations through the Public Communication Service in the Regional Office of The Legal and Human Rights Ministries of Bali, and what are the factors which affect the resolution of the allegations of Human Rights violations through the Public Communication Service in the Regional Office of The Legal and Human Rights Ministries of Bali. The research method used is empirical legal research. The results have shown that the Regional Office of the Legal and Human Rights Ministries of Bali in handling the allegations of human rights violations through the Public Communication Service has done such by using a mediation method and is acting as the mediator. Dugaan pelanggaran Hak Asasi Manusia di Provinsi Bali baik yang dilakukan secara vertikal oleh pemerintah maupun yang dilakukan secara horizontal oleh sesama masyarakat, ditandai dengan tingginya pengaduan masyarakat yang masuk ke tim Pelayanan Komunikasi Masyarakat pada Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Bali. Permasalahan yang diangkat dalam penelitian ini yaitu bagaimana mekanisme penyelesaian dugaan pelanggaran hak asasi manusia melalui pelayanan komunikasi masyarakat pada Kantor Kementerian Hukum dan Hak Asasi Manusia Bali dan faktor-faktor apa yang dapat mempengaruhi penyelesaian dugaan pelanggaran hak asasi manusia melalui pelayanan komunikasi masyarakat pada Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Bali. Metode penelitian yang digunakan adalah penelitian hukum empiris. Hasil penelitian menunjukkan bahwa Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Bali dalam menangani dugaan pelanggaran hak asasi manusia melalui pelayanan komunikasi masyarakat dilakukan dengan cara mediasi dan bertindak sebagai mediator.